1994
DOI: 10.5144/0256-4947.1994.399
|View full text |Cite
|
Sign up to set email alerts
|

A Seroepidemiological Study of Measles: Some Practical Implications for Measles Immunization Program, Kingdom of Saudi Arabia

Abstract: It was hypothesized that the recent outbreaks of measles in a geographically defined area of Al-Qassim might reflect significant changes in the epidemiology of measles and cast doubt upon the real protective value of measles vaccines. Therefore, the two objectives of this research were to study some epidemiological parameters of cases of measles (n=993) and the current immunological status of immunized children (n=2810). The crossmatched data about measles patients were collected on an official proforma and 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…We identified over 220 studies that provided cross‐sectional data and nearly 180 studies that reported on immunity for women of child‐bearing age, primarily for rubella. Table summarizes the over 400 cross‐sectional and women of child‐bearing age measles and rubella serological studies…”
Section: Resultsmentioning
confidence: 99%
“…However, the most important implication of this finding is that if this minority of nomadic children under five years of age is in fact not vaccinated in time (n=19.9, 89%), it might lead to future episodic outbreaks of several infectious diseases, for instance measles. 12 Globally, about 10% of nomads are not familiar with the concept of medical diseases and also the availability of therapeutic and curative services including primary healthcare services, hence they tend to seek non-medical pathways including traditional healers, as mentioned earlier, whose practices have yet to be studied scientifically. They in fact need an intensive awareness campaign via the media or alternative suitable ways such as providing relevant and basic public health information through lectures by their trained leaders or primary care physicians at their places of aggregation.…”
Section: Discussionmentioning
confidence: 98%